Mogrol Attenuates Osteoclast Formation and Bone Resorption by Inhibiting the TRAF6/MAPK/NF-κB Signaling Pathway In vitro and Protects Against Osteoporosis in Postmenopausal Mice - Chen, Yongjie; Zhang, Linlin; Li, Zongguang; Wu, Zuoxing; Lin, Xixi; Li, Na; Shen, Rong; Wei, Guojun; Yu, Naichun; Gong, Fengqing; Rui, Gang; Xu, Ren; et al. (Frontiers in Pharmacology, 2022)
Osteoporosis is a serious public health problem that results in fragility fractures, especially in postmenopausal women. Because the current therapeutic strategy for osteoporosis has various side effects, a safer and more effective treatment is worth exploring. It is important to examine natural plant extracts during new drug design due to low toxicity. Mogrol is an aglycon of mogroside, which is the active component of Siraitia grosvenorii and exhibits anti-inflammatory, anticancer and neuroprotective effects. Here, we demonstrated that mogrol dose-dependently inhibited osteoclast formation and function. To confirm the mechanism, RNA sequencing (RNA-seq), real-time PCR (RT–PCR), immunofluorescence and Western blotting were performed. The RNA-seq data revealed that mogrol had an effect on genes involved in osteoclastogenesis. Furthermore, RT–PCR indicated that mogrol suppressed osteoclastogenesis-related gene expression, including CTSK, ACP5, MMP9 and DC-STAMP, in RANKL-induced bone marrow macrophages (BMMs). Western blotting demonstrated that mogrol suppressed osteoclast formation by blocking TNF receptor-associated factor 6 (TRAF6)-dependent activation of the mitogen-activated protein kinase (MAPK)/nuclear factor-B (NF-κB) signaling pathway, which decreased two vital downstream transcription factors, the nuclear factor of activated T cells calcineurin-dependent 1 (NFATc1) and c-Fos proteins expression. Furthermore, mogrol dramatically reduced bone mass loss in postmenopausal mice. In conclusion, these data showed that mogrol may be a promising procedure for osteoporosis prevention or therapy.